Drying Properties and Rice Production Potential of Cracking Soils in the Muda Irrigation Scheme - Islam, Md. Tariful (1999)
Three previously puddled rice soils, namely the Chengai, Tebengau, and Tualang series of the Muda Irrigation Scheme were studied both in the field and in the glass house. The objectives of this study were to understand the processes of drying, cracking and re-wetting and relate these to soil properties, to develop a simple model for estimating bypass flow and bypass ratio of cracking soil during land soaking, and to simulate the ORYZA_ W model for determining the optimum sowing date, quantifying rice yield, net water use, and crop duration under future climate change scenarios, and assessing the drought effect on irrigated rice yield. Calculated volumetric and linear shrinkage of the Chengai and Tebengau series were similar and greater than those of the Tualang series. The measured shrinkage geometric factor rs, with values of around 3 , indicated that shrinkage of these three series was isotropic. Comparatively faster moisture depletion and absorption were observed in the Chengai and Tebengau series than in the Tualang series both in the glasshouse and field conditions. Chengai and Tebengau soils showed similar crack width, depth, area, length and volume, these properties being significantly different from those of the Tualang soil. The deepest crack depth below the puddled layer measured by the paint method were 77, 73, and 52 cm in the Chengai, Tebengau, and Tualang series, respectively. A model was developed to quantify bypass flow during land soaking. According to the model, the amount of water that bypassed the topsoil of the three soil series accounted for 59-67% of total input water. Higher yields (1 0.2 to 1 0.6 t ha-I) were predicted for the off season (56-98 Day of the Year - DOY) than the main season (9.2 to 9.7 t ha-I during 1 96-238 DOY). The higher off season yields were associated with higher radiation and longer crop duration. The impact of 15 different climatic scenarios was evaluated. Crop duration (TGP) was shortened by 3 and 2 days during the off and main seasons, respectively, following a 4°C increase in the daily maximum temperature. Increased CO2 levels predicted an increase in yield in both seasons. The combinations of increased CO2 levels and temperatures predicted increased yields for both seasons. The scenarios of three General Circulation Models (GCM) predicted yield reduction in the off season while in the main season, predicted yields were almost similar to current yields. The net water use (NWU) increased with increase in temperature in both seasons for all cases. Increments in CO2 level did not predict any change for NWU in both seasons. The combinations of increased temperatures and CO2 levels, and the scenarios of three GCMs predicted an increase of NWU in both seasons. Increased NWU was mainly influenced by temperature increments. Yield differences between crops temporarily stressed at mid-tillering and panicle initiation stages and nonstressed crops were smaller. However, maturity was delayed in both seasons. Large yield reductions were predicted for temporary drought stress at the flowering stage, while maturity was delayed by 3 and I-day in the off and main seasons, respectively.